Thermal Image Encryption Based on Region of Interest (ROI) and Chaotic map - B S, Lokesh; M B, Dr. Manjunatha (International Journal of Engineering and Technology, 2018)
Most of the thermal image information concentrated on a particular region and 50% of image information stored in Most Significant Bit (MSB) plane. Based on these two strategy, proposed an thermal image encryption based on region of interest (ROI) and chaotic map. Firstly extract the MSB bit plane of thermal input image. This Â MSB bit plane undergo ROI calculation method. This method involves the partition of MSB bit plane into several 16*16 blocks. Apply the thresholding function to each block to separate the ROI blocks. Then selected part from input thermal image undergo XOR operation between random image generated from chaotic map. For lossless decryption at the receiver side, embedded the index of ROI blocks using LSB embedding algorithm. Simulation results shows the proposed algorithm achieves good security and more efficiency.